P17. Early Huntington's disease patients demonstrate micro-structural and functional connectivity changes in motor and basal ganglia-thalamic networks. Issue 8 (August 2015) - Müller, H.-P.; Kassubek, J.; Grön, G.; Gorges, M.; Landwehrmeyer, G.B.; Süßmuth, S.D.; Orth, M.
<x xml:space="preserve">Abstract</x> Introduction In Huntington's disease (HD), cerebral white matter changes have been reported in a number of studies using diffusion tensor imaging (DTI) or T1-weighted magnetic resonance imaging (MRI). A key question is how brain structure changes (both grey and white matter) influence brain function. Intrinsic functional connectivity (ifc) MRI investigates intrinsic connectivity networks (ICN), i.e. large-scale distributed functionally coupled brain regions observed in the absence of a specific task. The objective of our study was to integrate structural connectivity data as assessed by DTI with ifcMRI changes in order to obtain a comprehensive picture of structural and functional changes with an emphasis on motor and basal ganglia thalamic networks. Methods Thirty-five early HD subjects (TFC stage 1 and 2) and 32 age- and sex-matched healthy controls underwent3T-MRI (T1w, DTI and ifcMRI sequences). DTI and ifcMRI data analyses were performed using the Tensor Imaging and Fiber Tracking (TIFT) software (Müller et al., 2007) for complementary DTI fiber tracking (FT) and ifcMRI data analysis. For the motor ICN ifcMRI analyses, the dominant M1 was used as the seed, for the basal ganglia-thalamic ICN the thalamus was used. In addition, the cortico-spinal tract (CST) and the thalamocortical pathway were used for comparisons at the group level. Results Structural connectivity measured by DTI at the group level showed an increase of FA values in the basal ganglia as well as FA reductions in the external and internal capsule, in parts of the thalamus, and in subcortical white matter. Intrinsic functional connectivity (brain function) showed hyper-connectivity in the motor ICN, i.e. the insula was less connected in HD than in controls. The basal ganglia-thalamic ICN connectivity differed between HD and controls in the insula and the basal ganglia in both hemispheres. Conclusion At the group level, we confirmed microstructural changes identified in previous DTI studies in HD (e.g. (Rosas et al., 2006)). There is evidence that the insula becomes disconnected from the motor cortex. The caudatum seems to lose its functional integration with widely distributed cortical areas (basal ganglio-thalamic ICN). Abnormal connectivity of the insula and caudatum may be relevant in the emergence of clinical signs of HD. Acknowledgements This work was partially supported by the <funding-source id="gp005" xlink:type="simple" xlink:role="http://www.elsevier.com/xml/linking-roles/grant-sponsor" xlink:href="" xmlns:xlink="http://www.w3.org/1999/xlink">European Union</funding-source> under the Seventh Framework programme - PADDINGTON Project, Grant Agreement No.261358, and the European Huntington's Disease Network (EHDN), project 070 - PADDINGTON.